An exploratory qualitative study of the experiences of women in volunteer non-player roles in Australian community football clubs - Morgan, Joanne M.; Lovell, G. P.; Tulloch, K. (Frontiers in Sports and Active Living, 2024)
Women are underrepresented in volunteer non-player roles in community sporting clubs, particularly in traditionally male sports such as football (soccer), where participation rates for men and boys remain higher than women and girls. Experiences of women volunteering in community sporting clubs are not well-represented in research literature. By exploring women's experiences volunteering in community Australian Football clubs, the present research aimed to understand the barriers and facilitators of women's participation in volunteer non-player community sport club roles. Our intention is that our findings will provide empirical basis for the design of efficacious evidence-based interventions and initiatives to help close the gender gap of volunteerism rates and experiences, thus facilitating equal opportunities for women to access associated individual social, physical, and mental health benefits of sports volunteering. We conducted individual semi-structured interviews with six women from four Australian Football clubs, to determine barriers and facilitators to volunteering. Reflexive thematic analysis of barriers generated six themes: high expectations of self, intersectionality (of gender with motherhood or race), constrained resources, interpersonal disconnection, lack of organisational support and structure, and gender role assumptions and stereotypes. Analysis of facilitators produced six themes: having or building confidence, positive reinforcement, social connection, deliberate efforts to engage women, role autonomy and shaping, and supportive culture within a club or governing body. Findings revealed that impacts on women's development in non-player roles exist at the individual level, including the interaction of gender, race, and parental status, but also extend beyond this to personal, interpersonal, organisational, and sociocultural factors. Given our research findings we make seven recommendations for governing bodies and community football clubs to enhance volunteering gender equity: 1.Establish support for women by dividing work evenly among volunteers; 2.Provide clear descriptions of non-player roles; 3.Match the skill sets of new women volunteers to suitable roles; 4.Implement mentorship programs to aid collaboration among women who volunteer; 5.Educate communities about gender biases and assumptions; 6.Monitor and seek feedback on gendered task allocation to ensure women's unpaid labour is not disproportionate to men's; and 7.Promote and publicise women in nonplayer roles to enhance women's visibility and acceptance in community football clubs.